2022
DOI: 10.3390/su142315694
|View full text |Cite
|
Sign up to set email alerts
|

Streamliners, Switchmen and Bridge Builders: About the Mechanisms and Uniqueness of Accelerator Programs

Abstract: Accelerators are a new and fast-growing element in entrepreneurial ecosystems. However, our understanding about their impact on the development of startups remains limited. Utilizing a grounded theory approach and in-depth interviews with 21 entrepreneurs, this study investigates the value-adding mechanisms of accelerators. Our analysis, however, is not limited to financial capital, which allows us to highlight the relative importance of different forms of capital in the context of accelerators. We aim to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 159 publications
(302 reference statements)
0
4
0
Order By: Relevance
“…By providing workshops and seminars delivered by directors, mentors and guest speakers, and providing arenas for presentations and feedback, accelerators seek to increase the likelihood of the entrepreneurs making wellinformed decisions and at avoiding potential pitfalls in the venturing process (Cohen et al, 2019;Hallen, Bingham, & Cohen, 2016). Indeed, research shows that accelerators not only advise entrepreneurs in the quality and validity of their business ideas, but also by questioning many fundamental assumptions about the execution of their business ideas (Ulmer & Pape, 2022). As entrepreneurial climate and learning from peers are considered important factors in acceleration, admitted start-ups move their businesses to accelerator headquarters for the duration of the program.…”
Section: Accelerators As Identity Shapersmentioning
confidence: 99%
See 3 more Smart Citations
“…By providing workshops and seminars delivered by directors, mentors and guest speakers, and providing arenas for presentations and feedback, accelerators seek to increase the likelihood of the entrepreneurs making wellinformed decisions and at avoiding potential pitfalls in the venturing process (Cohen et al, 2019;Hallen, Bingham, & Cohen, 2016). Indeed, research shows that accelerators not only advise entrepreneurs in the quality and validity of their business ideas, but also by questioning many fundamental assumptions about the execution of their business ideas (Ulmer & Pape, 2022). As entrepreneurial climate and learning from peers are considered important factors in acceleration, admitted start-ups move their businesses to accelerator headquarters for the duration of the program.…”
Section: Accelerators As Identity Shapersmentioning
confidence: 99%
“…In another study, Tobiassen, Elvekrok, and Skreosen (2022) found that entrepreneurs participating in an accelerator program tended to experience tension in the feedback and mentoring processes that seemed to trigger identity reflection. Ulmer and Pape (2022) found that participants in an accelerator program started to self-identify as founders (entrepreneurs) during the program. Hence, new self-confidence and enhanced passion for the entrepreneurial journey prepared the entrepreneurs for their leading role in the new venture development (Ulmer and Pape, 2022).…”
Section: Accelerators As Identity Shapersmentioning
confidence: 99%
See 2 more Smart Citations